Cardiometabolic Risk in First Episode Psychosis Patients - Smith, Jo; Griffiths, Lisa A.; Band, Marie; Horne, Dominic (Frontiers in Endocrinology, 2020)
Previous research in patients with schizophrenia in European and USA population groups has demonstrated a high prevalence of metabolic syndrome and disease progression (~35%–40%) and increased risk for cardiovascular disease and long-term mortality. Limited research has determined the prevalence of existing cardiometabolic risk factors at onset of a first episode psychosis. This cross-sectional study presents a clinical overview of the cardiometabolic risk profile in young people with first episode psychosis in the UK. Forty-six participants (72% male) clinically diagnosed with first episode psychosis (n = 25), schizophrenia (n = 13), bipolar disorder (n = 4), unspecified non-organic psychosis (n = 2) or acute psychotic episode (n = 2) with < 6 months Duration of Untreated Psychosis (DUP; mean 33.4 ± 37.2 days) were assessed for anthropometric, health risk behaviors and clinical measurements including resting heart rate, blood pressure, blood lipids, glycated hemoglobin, and prolactin. Overall, participants (aged 18–37 years) had a high prevalence of cardiometabolic risk factors due to: elevated values for BMI (73%) and abdominal adiposity (50%), blood pressure (47% prehypertensive; 23% hypertensive), resting heart rate (43%); hypercholesterolemia (32%); suboptimal HDL-C levels (36%); and hypertriglyceridemia (40%). Participants also self-reported poor health risk habits including smoking (55%), alcohol use (39%), substance use (18%), poor diet (52%), and sedentary behavior (29%). Young people with psychosis are at increased risk for cardiometabolic disorders due to elevated clinical markers and health risk behaviors. Physical health interventions (including health behavior advice) are needed early in the treatment process to address this increased risk for cardiometabolic disorders in individuals recently diagnosed with psychosis.